Approaches Towards Effective Knowledge Management for Small and Medium Enterprises in Developing Countries - Uganda - Habinka, Annabella; Sol, Henk; Baryamureeba, Venansius (IIMC International Information Management Corporation, 2009)
In developing countries, many Small and Medium Enterprises (SMEs) collapse due to complex factors. Knowledge shortage and fragmented information are their key challenges as a result of obsolete technology and exposure. However, the Government of Uganda plans to establish nationwide knowledge service centres in its Vision 2035 [9]. Viable solutions are at stake for developing countries. However, to enable them leap frog into the future, ICT is the remedy for knowledge sharing. SME survival is determined by the amount of knowledge they have and how they manage it in decision making. This paper promotes the studio based approach as a practical solution to SMEs asymmetric knowledge sharing. The studio will provide decision enhanced services to SME stakeholders and supplement techno-centric, social-cultural-centric and access-centric approaches. This paper aims at providing a theoretical backup for studio usage as a feasible solution for SMEs in developing countries.
Keywords: Knowledge Management; SMEs; Studio